2021
DOI: 10.1016/j.jbc.2021.100317
|View full text |Cite|
|
Sign up to set email alerts
|

Enterovirus D68 molecular and cellular biology and pathogenesis

Abstract: In recent years, enterovirus D68 (EV-D68) has advanced from a rarely detected respiratory virus to a widespread pathogen responsible for increasing rates of severe respiratory illness and acute flaccid myelitis (AFM) in children worldwide. In this review, we discuss the accumulating data on the molecular features of EV-D68 and place these into the context of enterovirus biology in general. We highlight similarities and differences with other enteroviruses and genetic divergence from own historical prototype st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 229 publications
0
21
0
Order By: Relevance
“…A recent study on the use of fluoxetine in patients with AFM found that fluoxetine was well tolerated and safe. In addition, immune suppressive therapies have also been used by some centers to target the inflammatory response to infection [ 131 ]. It should be noted that recently much progress has been made in the development of the EV-D68 antivirals by targeting various viral proteins and host factors essential for viral replication [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on the use of fluoxetine in patients with AFM found that fluoxetine was well tolerated and safe. In addition, immune suppressive therapies have also been used by some centers to target the inflammatory response to infection [ 131 ]. It should be noted that recently much progress has been made in the development of the EV-D68 antivirals by targeting various viral proteins and host factors essential for viral replication [ 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, most antiviral research has targeted this virus. Several antiviral strategies have been proposed (reviewed in References [ 165 , 166 ]) such as capsid-binding compounds [ 145 , 167 , 168 , 169 , 170 , 171 ], viral proteases’ inhibitors [ 168 , 169 , 172 , 173 , 174 ], drugs targeting the non-structural proteins 2C [ 168 , 175 , 176 ], 3A [ 167 , 168 , 169 , 177 ], the viral polymerase 3D [ 167 , 169 , 178 , 179 ] and drugs blocking translation [ 180 ]. However, even the most favourable candidates did not obtain promising results in the mouse models [ 175 , 181 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses of contemporary versus prototype EV-D68 strains have revealed significant genetic viral evolution over time. Studies in vitro have characterized several functional impacts of these changes on host cell receptor usage and viral RNA metabolism that may contribute to expanded tissue tropism and increased virulence in vivo (reviewed in reference 3 ). Still, there are significant gaps in our understanding of EV-D68 pathogenesis in vivo , including knowledge of target cell types, mechanisms of systemic viral dissemination and tissue-specific infection, host innate and adaptive immune responses, and the relative contributions of both virus- and host-specific factors in disease progression and severity.…”
Section: Introductionmentioning
confidence: 99%